The Relationship Between Family Support And The Self-Concept Of Prisoners In The State Detention Center (RUTAN) Class 1 Labuhan Deli Medan - Fitriani Fadillah (Institute of Computer Science (IOCS), 2021)
Prisoners are a form of life that is difficult to accept, both by themselves and by others in the community, many families of convicts who do not provide support for prisoners are even neglected, so researchers are interested in researching the relationship between family support and self-concept of prisoners at home. State Prisoners (RUTAN) Class 1 Labuhan Deli Medan in 2022. This study uses direct observational research, namely data collection by direct observation of respondents with a cross-sectional time approach. ) Class 1 Labuhan Deli Medan which amounted to 436 people in May 2022, the sampling method in this study was carried out using purposive sampling as many as 81 people, test data analysis with statistical tests in this study, used the chi square formula (kai squared). The results of this study There is a significant relationship between family support and self-concept of prisoners in the Class 1 State Detention Center (RUTAN) Labuhan Deli Medan in 2022, with a p value = 0.000 (p <0.05). The conclusion in this study from this means that the higher the family support provided, the more positive the self-concept of prisoners in the Class 1 State Detention Center (RUTAN) Labuhan Deli Medan. Suggestions The results of this study can provide additional information, especially mental and community nursing practices in providing mental nursing services in certain communities that are alienated from society such as prisoners in the Class 1 State Detention Center (RUTAN) Labuhan Deli Medan who require holistic (holistic) services. especially mental nursing services so that people